Karakteristik Kawasan Wisata Pantai Taula'a Kecamatan Bilato Kabupaten Gorontalo Provinsi Gorontalo - Samin Maharuju; Fitryane Lihawa; Syahrizal Koem (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2023)
Collaborative practices in the management of Taulaa Beach have not been maximized, including the minimal role of the community in beach maintenance and the lack of facilities and accessibility. This study aimed to assess the appropriateness of tourism in the Taula'a Beach area, located in the Bilato District of the Gorontalo Regency, inside the Gorontalo Province. The chosen research methodology entails the utilization of a survey-based approach. The process of data acquisition via direct observation and field measurements. The criteria that determine the acceptability of a tourism destination include water depth, beach type, beach breadth, water base material, current speed, beach slope, water brightness, land cover, presence of harmful biota, and availability of fresh water. The appropriateness of beach tourism is analyzed using the Tourism Suitability Index (IKW). The research findings yielded an IKW value of 77.4%. This value indicates that land suitability in the Taula'a Beach Tourism Area is included in the very suitable classification, specifically in the S1 category.